Optimalisasi Kebijakan Perlindungan Lingkungan Untuk Pengelolaan Sumber Daya Alam Berkelanjutan - Qutbi, Acik Ardiansyah; Sarjan, Muhammad (Lembaga Bale Literasi, 2024)
Human life and the sustainability of the earth's ecosystem depend heavily on wise management of natural resources. Limited natural resources and negative impacts on the environment require optimal environmental protection policies. This research aims to identify, analyze and propose strategic steps in improving environmental protection policies to support sustainable natural resource management. The research methodology involves literature analysis, case studies of environmental policies, as well as an assessment of the impact of current policies on the environment and sustainability of natural resources. The results of the analysis show that there is a need to increase coordination between the government, industrial sector and society in formulating and implementing environmental protection policies. In this context, a participatory and sustainability-based approach must be the main basis in developing new policies. The proposed strategic steps include strengthening regulations, increasing public understanding, empowering local communities, and increasing investment in environmentally friendly technology. Additionally, this research highlights the importance of a cross-sectoral approach in addressing complex environmental protection challenges. By implementing these strategic steps, it is hoped that environmental protection policies can be optimized to support sustainable natural resource management. The practical implication of this research is to provide guidance for policy makers, stakeholders and the general public to jointly contribute to maintaining ecosystem balance and improving the quality of life for future generations.